Correlating the switch-on time of two identical PV modules using a simplified measuring approach - Swart, Arthur James (IEEE Explore: Electrical Engineering/Electronics, Computer, Telecommunications and Information Technology (ECTI-CON), 2016 13th International Conference, 2016)
The installation of different renewable energy systems is gaining momentum globally, as governments and industry seek to reduce carbon emissions and fossil fuel usage. PV systems have become more common place, as evidenced by the number of PV array roof-installations visible in many communities today. However, it is assumed that the modules in these arrays are identical, as it is important to have similar currents flow through each branch of an array. Partial shading or unmatched PV modules may lead to power mismatches, hot spots and ultimately a lower overall output power than what is desired. The purpose of this paper is to present a simplified measuring approach to validate the operating performance of two identical PV modules by determining their switch-on time. Any significant differences in switch-on time between identical PV modules could lead to possible power mismatches in a PV array. Results confirm that both PV modules are very similar in switch-on time, with an average on-time difference of 2 minutes and 27 seconds.. This indicates that both PV modules start operating at roughly the same time of the day, thereby providing similar current flows which contribute to the optimum performance of a PV array.
Published Conference Proceeding
Keywords: shading; mismatch; Webcam; motion-detection